EFFECT OF MAULI BANANA STEM EXTRACT-CA(OH)2 COMBINATION ON WATER SOLUBILITY AND ABSORPTION AS A POTENTIAL PULP CAPPING MATERIAL - Agung Satria Wardhana; Dewi Puspitasari; Debby Saputera; Rahmad Arifin; Pindobilowo Pindobilowo; Rosihan Adhani (Dentino: Jurnal Kedokteran Gigi, 2025)
Background: Calcium hydroxide [Ca(OH)2] is the gold standard material in pulp capping treatment due to reparative dentin formation and antibacterial. However, Ca(OH)2 deficiency forms reparative dentin with tunnel defects and is easily soluble in water and acid. Mauli banana stem extract (MBSE) functions as an antibacterial and anti-inflammatory and is expected to form better reparative dentin. The combination of Ca(OH)2 and MBSE is assumed to be able to improve the physical properties of Ca(OH)2. Purpose: to analyze the effect of 50% MBSE+ Ca(OH)2 combination on solubility and water absorption as a pulp capping material. Methods: The group were combination of MBSE+Ca(OH)2+PG (1.5:1:0.375), (1:1.5:0.375) and  Ca(OH)2 + aquadest (1:1). Each group consisted of 5 samples with 6 groups and 2 tests, a total of 60 samples with dimensions of 15 mm x 1 mm. Samples were measured for solubility and water absorption ability by weighing before and after dissolving in 50 mL of artificial saliva for 24 hours, drying, incubating, and weighing a second time. The result of the mass reduction divided by the volume of the sample was considered as the solubility and water absorption rate in 1 and 7 days. The data was analyzed using One Way Anova with significant difference <0.05. Results: The solubility of MBSE+Ca(OH)2+PG at (1.5:1:0.375) and (1:1.5:0.375)was lower than Ca(OH)2+aquadest (1:1) after immersion for 1 day and 7 day. The water absorption of MBSE+Ca(OH)2+PG (1.5:1:0.375) was not different from Ca(OH)2+aquadest (1:1) after immersion  for 1 day, but higher in 7 day (p<0,05). Conclusion: The solubility of the MBSE-Ca(OH) combination is lower than Ca(OH)2 alone, the water absorption of the MBSE- Ca(OH)2 combination is higher than that of Ca(OH)2 alone.